MICROSCOPIC STRUCTURE OF THE HEMOMICROCIRCULATORY STREAM OF NORMAL HUMAN FRONTAL SINUS INFERIOR WALL MUCOSA - Fomina, L.V. (World of Medicine and Biology, 2016)
The paper studied the microscopic structure hemomicrocirculatory channel bottom wall of the frontal sinus mucosa. In the study it was found that the blood supply is provided hemomicrocirculatory riverbed, which is defined by two main components: the superficial microvessels that provide trophism epithelium and deep vascular net, which is localized in the lamina propria of connective tissue presented arteries and veins. The greatest features of all vessels were found in the arterioles, which are characterized by a significant number of smooth muscle cells (4-6 layers in comparison with 1-2 layers) at a middle shell arterioles compared to the front wall of the frontal sinus. It has been found that the general features of the structure hemomicrocirculatory channel bottom wall of frontal sinus mucous membrane may be compared with the structure of other vascular mucous membranes of the paranasal sinuses.